Testing j-curve effect on trade balance in Turkish economy - Zubeyir Can Kansel; Bilgin Bari (Financial Studies, 2020)
This study researches the effects of changes in the exchange rate on the trade balance after the transition to the floating exchange rate in the Turkish economy. For this purpose, ARDL and ECM models have been developed by using quarterly data from 2003 through 2018. The starting point of the research is to examine the validity of the J-Curve theory in the Turkish economy. According to the results of the analysis of the main model used in the study, there is no J-Curve effect on the trade balance in the related period. The results state that the effect of changes in exchange rates on the foreign trade balance is limited. The main reason for that is the high usage of imported intermediate goods and inputs in production. The results of analysis show that the fundamental structural problem of Turkey's economy is the usage of imported intermediate goods and inputs. Therefore, the effect of the exchange rate on trade balance differs from theoretical expectations. The main policy result of the study is that foreign trade balance might be improved by increasing the usage of domestic intermediate goods and inputs in production
Keywords: C32; F31; F41; 330; Trade Flows; Real Effective Exchange Rate; ARDL model; Cointegration; Trade Flows